Loss of β2-spectrin prevents cardiomyocyte differentiation and heart development. (24th September 2013) - Lim, Jeong A.; Baek, Hye Jung; Jang, Moon Sun; Choi, Eun Kyoung; Lee, Yong Min; Lee, Sang Jin; Lim, Sung Chul; Kim, Joo Young; Kim, Tae Hyun; Kim, Hye Sun; Mishra, Lopa; Kim, Sang Soo
Abstract: Aims: β2-Spectrin is an actin-binding protein that plays an important role in membrane integrity and the transforming growth factor (TGF)-β signalling pathway as an adaptor for Smads. Loss of β2-spectrin in mice ( Spnb2 −/− ) results in embryonic lethality with gastrointestinal, liver, neural, and heart abnormalities that are similar to those in Smad2 +/− Smad3 +/− mice. However, to date, the role of β2-spectrin in embryogenesis, particularly in heart development, has been poorly delineated. Here, we demonstrated that β2-spectrin is required for the survival and differentiation of cardiomyocytes, and its loss resulted in defects in heart development with failure of ventricular wall thickening. Methods and results: Disruption of β2-spectrin in primary muscle cells not only inhibited TGF-β/Smad signalling, but also reduced the expression of the cardiomyocyte differentiation markers Nkx2.5, dystrophin, and α-smooth muscle actin (α-SMA). Furthermore, cytoskeletal networks of dystrophin, F-actin, and α-SMA in cardiomyocytes were disorganized upon loss of β2-spectrin. In addition, deletion of β2-spectrin in mice ( Spnb2 tm1a/tm1a ) prevented proper development of the heart in association with disintegration of dystrophin structure and markedly reduced survival. Conclusion: These data suggest that β2-spectrin deficiency leads to inactivation of TGF-β/Smad signalling and contributes to dysregulation of the cell cycle, proliferation, differentiation, and the cytoskeletal network, and it leads to defective heart development. Our data demonstrate that β2-spectrin is required for proper development of the heart and that disruption of β2-spectrin is a potential underlying cause of congenital heart defects.